The Effects of Modified Atmosphere Packaging on Toxin Production by Clostridium botulinum in Raw Aquacultured Flounder Fillets and Fully Cooked Breaded and Battered Pollock Portions - Arritt, Fletcher M. III (Virginia Tech, 2004)
Fish products under vacuum (VAC) and/or modified atmosphere packaging (MAP) conditions can have a significantly extended shelf life. Prevention of toxin production by Clostridium botulinum is essential for processors of VAC and MAP refrigerated fishery products. The objective of this study was to determine if C. botulinum toxin development precedes microbiological spoilage and sensory rejection in fully cooked breaded and battered Alaskan Pollock or raw aquacultured flounder fillets. Aquacultured summer flounder (Paralichthys dentatus) fillets and fully cooked breaded and battered Alaskan pollock (Theragra chalcogramma) were either aerobically packed (Oxygen Transmission Rate (OTR) of 3,000 cc/m2/24h@70°F for flounder and 6,000 cc/m2/24h@70°F for Pollock), vacuum packed or MAP packaged in a 100% CO atmosphere (OTR of 7.3 cc/m2/24h@70°F). Flounder fillets were stored at either 4 or 10°C while pollock portions were stored at 8 and 12°C. Based on the time to spoilage (counts >107 CFU/g), additional samples were inoculated with five strains of nonproteolytic C. botulinum and analyzed qualitatively for botulinum toxin using a mouse bioassay. For flounder at 4°C, toxin formation did not occur after 35 days in aerobically packed fillets. Vacuum packed and 100% CO2 fillets produced toxin before spoilage at days 20 and 25, respectively. In the aerobic packages at 10°C, toxin production occurred after spoilage at day 8, but before spoilage in the vacuum and 100% CO packages at day 9. Sensory evaluation of toxic vacuum and 100% CO packages at 4°C revealed toxin production proceeded spoilage and absolute sensory rejection. However, at 10°C toxin production was evident only after absolute sensory rejection and microbiological spoilage for aerobically packed fillets. Vacuum packages and 100% CO packages were toxic during spoilage but before absolute sensory rejection. Toxin was not present in the aerobically and 100% CO packed pollock samples at 8°C and the 100% CO2 packed samples at 12°C after 35 days. Aerobically packed ...